Connection between Lithium Coordination and Lithium Diffusion in [Pyr12O1][FTFSI] Ionic Liquid Electrolytes. Issue 12 (5th February 2018) - Giffin, Guinevere A.; Moretti, Arianna; Jeong, Sangsik; Pilar, Kartik; Brinkkötter, Marc; Greenbaum, Steven G.; Schönhoff, Monika; Passerini, Stefano
Abstract: The use of highly concentrated ionic liquid‐based electrolytes results in improved rate capability and capacity retention at 20 °C compared to Li + ‐dilute systems in Li‐metal and Li‐ion cells. This work explores the connection between the bulk electrolyte properties and the molecular organization to provide insight into the concentration dependence of the Li + transport mechanisms. Below 30 mol %, the Li + ‐containing species are primarily smaller complexes (one Li + cation) and the Li + ion transport is mostly derived from the vehicular transport. Above 30 mol %, where the viscosity is substantially higher and the conductivity lower, the Li + ‐containing species are a mix of small and large complexes (one and more than one Li + cation, respectively). The overall conduction mechanism likely changes to favor structural diffusion through the exchange of anions in the first Li + solvation shell. The good rate performance is likely directly influenced by the presence of larger Li + complexes, which promote Li + ‐ion transport (as opposed to Li + ‐complex transport) and increase the Li + availability at the electrode. Abstract : Ain′t no complex that moved : The good rate performance of Li‐ion cells with high concentration ionic liquid electrolytes is likely directly influenced by the presence of larger Li + complexes, which promote Li + ‐ion transport through structural diffusion and increase the Li + availability at the electrode.